ANALISIS YURIDIS KEDUDUKAN ANAK ANGKAT DITINJAU DARI HUKUM ADAT MANDAILING DI KECAMATAN PANYABUNGAN UTARA - WAHDAH NORA HARAHAP (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING: 1. Muhd Yamin 2. Syafruddin Kalo 3. SaidinAdoption is a legal act which transfers a child from their parents’ authority, legal guardian, or other people who are liable for their caring, education and raising the child in to an adopted family. It is no longer a strange thing in today’s Indonesian society because adopting child has been frequently done in Indonesia.The results of the research demonstrate that the factors that encourage child adoption in Mandailing community in Panyabungan Utara Subdistrict is to pass on and maintain a lineage of the family who does not have any biological child, to maintain marital bond so that a divorce can be prevented. However, the motivation of child adoption has been developed today; it is now done to provide the adopted child prosperity.Keywords: Adopted Child, Position, Customary Law of Mandailing